Antibiotic prescriptions in acute otitis media and pharyngitis in Italian pediatric outpatients - E. Barbieri; D. Donà; A. Cantarutti; R. Lundin; A. Scamarcia; G. Corrao; L. Cantarutti; C. Giaquinto (BMC, 2019)
Abstract Background Acute otitis media (AOM) and pharyngitis are very common infections in children and adolescents. Italy is one of the European countries with the highest rate of antibiotic prescriptions. The aim of this study is to describe first-line treatment approaches for AOM and pharyngitis in primary care settings in Italy over six years, including the prevalence of 'wait and see' for AOM, where prescription of antibiotics is delayed 48 h from presentation, and differences in prescribing for pharyngitis when diagnostic tests are used. Methods The study is a secondary data analysis using Pedianet, a database including data at outpatient level from children aged 0-14 in Italy. Prescriptions per antibiotic group, per age group and per calendar year were described as percentages. "Wait and see" approach rate was described for AOM and pharyngitis prescriptions were further grouped according to the diagnostic test performed and test results. Results We identified 120,338 children followed by 125 family pediatricians between January 2010 and December 2015 for a total of 923,780 person-years of follow-up. Among them 30,394 (mean age 44 months) had at least one AOM diagnosis (n = 54,943) and 52,341 (mean age 5 years) had at least one pharyngitis diagnosis (n = 126,098). 82.5% of AOM diagnoses were treated with an antibiotic within 48 h (mainly amoxicillin and amoxicillin/clavulanate) and the "wait and see" approach was adopted only in 17.5% of cases. The trend over time shows an increase in broad spectrum antibiotic prescriptions in the last year (2015). 79,620 (63%) cases of pharyngitis were treated and among GABHS pharyngitis confirmed by rapid test 56% were treated with amoxicillin. The ones not test confirmed were treated mainly with broad spectrum antibiotics. Conclusions Despite guidance to use the 'wait and see' approach in the age group analyzed, this strategy is not often used for AOM, as previously noted in other studies in hospital settings. Broad-spectrum antibiotic prescription was more frequent when pharyngitis was not confirmed by rapid test, in keeping with evidence from other studies that diagnostic uncertainty leads to overuse of antibiotics.